PENGARUH PENGGUNAAN MEDIA KONKRET TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN BAHASA INDONESIA KELAS I SD INPRES BAROMBONG 2 KOTA MAKASSAR - Femilianita; Andi Sukri Syamsuri; Muhammad Akhir (LPPM Universitas Cipta Mandiri, 2024)
The purpose of this research is to determine the effect of using concrete media on the learning outcomes of Class 1 students at SD Inpres Barombong 2 Makassar City in Indonesian language subjects for the 2023 academic year. This type of research is quazy-experimental research in the form of Pre-Test Post Test. Design experiments on This research involved 2 classes as an experimental class and a comparison class (control class). The sampling technique used was a saturated sample, by making the population a sample of 40 students. Data collection techniques in this research used tests and observation. The data analysis used is descriptive data analysis and inferential data analysis. The results of inferential statistical analysis using the normality test and homogeneity test of student learning outcomes taught using concrete media, obtained a significant value for the pretest of 0.969 and for the posttest, namely 0.964, the significant value obtained was greater than 0.05 (α>0.05) so that the data is normally distributed. The homogeneity test obtained sig 0.93, the significant value is greater than 0.05, so the variance between the pretest and posttest classes is the same (homogeneous). This means that the use of concrete media has an effect on student learning outcomes in Indonesian language classes. I SD Inpres Barombong 2 Makassar city